MILK PRODUCTION AND BUSINESS ANALYSIS ON DAIRY CATTLE AFFECTED BY PMK IN “KAMPOENG TERNAK” SIDOARJO LIVESTOCK: A LITERATURE REVIEW - Winda Ayu Puteri Sumartono; Sri Hidanah; Ira Sari Yudaniayanti; Widya Paramita; Moh Anam Al Arif; Imam Mustofa (Lafadz Jaya Publisher, 2023)
mineral superboosters and concentrating immunoboosters in the feed. This research was conducted on the smallholder dairy cattle in